Reading and Writing Development in Inclusive Settings: Teachers’ Perception of the Use of Digital Technology - Lénia Carvalhais; Paula Vagos; Lídia Ferreira Cerejeira; Teresa Limpo (Behavioral Sciences)
Reading and writing are foundational skills throughout school grades that could be improved using digital technology, especially in inclusive contexts. The present study aimed to understand primary teachers’ use of technology and their self-efficacy perception in the use of digital technology in inclusive settings, considering their application of universal, selective, or additional measures. In total, 290 Portuguese primary school teachers (1st to 4th grades) aged 25 to 66 years old (M = 49.32, SD = 8.59), mostly female, filled in an online survey, comprising a sociodemographic sheet and four questionnaires related to digital technologies. The results show that most teachers apply measures within the inclusive education framework (n = 277). The sociodemographic and educational profiles of teachers who use or do not use those technologies were similar, as were teachers’ self-efficacy scores about using digital technologies, perception about the utility of those technologies, and use of them, overall and for reading and writing specifically. The more teachers consider themselves efficacious in using digital technologies and the more they hold a positive perception of those technologies, the more they report their use. These findings reinforce the influence of teachers’ internal factors, such as self-efficacy, on the use of digital technologies, independent of students’ specific difficulties.